The integration of science and practice in one training program: Outcomes of a manualized career counseling group. - Leuty, Melanie E.; Bullock-Yowell, Emily; Womack, Anna; Schmidtman, Emily; Paulson, Deirdre; Andrews Wiebusch, Lindsay; Osborne, Lauren K. (Counselling Psychology Quarterly, 2015)
An example of training Counseling Psychology graduate students in integrating science and practice is detailed through the presentation of the development, implementation, and evaluation of a Cognitive Information Processing approach-based career counseling group. Pilot data on initial group outcomes is presented and involves a sample of 59 undergraduate students that participated in the five-session intervention developed by faculty and students. Following the intervention, participants reported significant decreases in negative thinking and significant increases in career decision-making self-efficacy. The continued development of this collaboration and benefits of involving students in their training as scientist-practitioners is discussed.